Thiadiazolo-azaacenes - Müller, Matthias; Koser, Silke; Tverskoy, Olena; Rominger, Frank; Freudenberg, Jan; Bunz, Uwe H. F. (Chemistry - a European journal, 2019)
This work reports the synthesis and characterization of bis- and tetrakis(thiadiazolo)-appended di- and tetraazaacenes, displaying up to seven catenated benzene/pyrazine rings. The targets are obtained by condensation of benzo-bis(thiadiazole)-4,5-dione with aromatic di- and tetraamines. The condensation products—up to a heptacene-like species—are stable but can be insoluble. Soluble derivatives are readily processible, but do not show enhanced electron affinities, as the two or four attached benzothiadiazole units are effectively resonance-separated from the acene body, maximizing the number of Clar-sextets.
Gesehen am 27.03.2020